Türk kültür tarihine giriş - Ögel, Bahaeddin, 1924-1989. (Ankara Ankara Ankara)
<7> cilt (1. c. xvi, 495 sayfa ; 2. c. xxiii, 527 sayfa ; 3. c. xv, 376 sayfa ; 4. c. xvi, 456 sayfa ; 5. c. xv, 440 sayfa ; 7. c. xxi, 412 sayfa ; 8. c. xi, 516 sayfa)